Effectiveness of Group Counseling Services Based on Rational Emotive Behavior Therapy (REBT) in Overcoming Social Anxiety Among Boarding Students - Siti Nasiyah; Wisnu Kurniawan; Siti Arifah (Journal of Cultural Guidance and Counseling, 2025)
This study aims to determine the effectiveness of Rational Emotive Behavior Therapy (REBT) in reducing social anxiety among university students. The research employed a quantitative method with a one-group pretest–posttest design. The participants were students experiencing moderate to high levels of social anxiety. Data were collected using a social anxiety scale that had been validated and tested for reliability, yielding a reliability coefficient of 0.884. The normality test showed a significance value of 0.200, indicating that the data were normally distributed. Hypothesis testing using a paired sample t-test in SPSS 23 for Windows resulted in a significance value (2-tailed) of 0.00 < 0.05, signifying a significant reduction in social anxiety after the intervention. The findings highlight that REBT not only effectively reduces negative irrational beliefs but also strengthens students’ confidence in social interactions within academic environments, especially those adapting to structured educational settings such as boarding systems. This demonstrates a contextual novelty compared to previous studies conducted on general student populations. Therefore, implementing REBT-based group counseling is highly recommended as a counseling intervention in higher education. Future research may expand by comparing boarding and non-boarding student populations, employing a control group, or incorporating follow-up assessments to evaluate the long-term effectiveness of REBT interventions